Bumpy road ahead : the automotive interiors merger that wasn't - Sousa, Milton; Comiteau, Lauren (London : Rotterdam School of Management, Erasmus University, 2015)
This case is about the merger & acquisition (M&A) process between American Automotive, Inc. (Smiths) and BarcelonaBrand Auto, Inc. (BBA). While the case is written in a fictional style, it is inspired by a real story with many similarities to what is portrayed. The case takes place within the automotive components industry and describes an acquisition and later merger between a much larger company, based in the USA, selling standard automotive components and a much smaller company based in Spain, selling customized automotive components for the luxury segment. What seemed to be a great strategic deal turned out to be an integration nightmare highlighting the importance of understanding national and company cultures, different leadership styles, deal valuation and specific distinctions in business models in M&A. The key question of the case is: what had gone wrong in this merger in such a little time?
Originally Published InSousa, M., & Comiteau, L. (2015). Bumpy Road Ahead: The Automotive Interiors Merger that Wasn't. Rotterdam, Netherlands: Rotterdam School of Management, Erasmus University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Automobile industry and trade -- Mergers